Physicochemical characterisation of biosynthetic bacterial cellulose as a potential wound dressing material - Abhishek Gupta; Wan Li Low; Stephen Britland; Iza Radecka; Claire Martin (University of Huddersfield Press, 2018)
The aim of this study was to characterise the physicochemical and biocompatibility properties of biosynthetic bacterial cellulose (BC) as a potential wound dressing material. The moisture content, water vapour transmission rate (WVTR), thermal stability, cyto- and haemo-compatibility of BC were investigated. Results indicated that the physicochemical properties of biosynthetic BC allow an optimum WVTR to be maintained for improved localised wound moisture levels, good thermal stability and excellent water imbibing capabilities. In vitro cytotoxicity and haemocompatibility confirmed the biocompatibility of BC and hence suitability of this material for further exploration into its' application as a wound dressing material.